Application of 5V spinel material LiNi0.5Mn1.5O4 in Li-ion batteries: single crystalline or polycrystalline?. Issue 18 (20th April 2023) - Jin, Jia; Wei, Jinping; Zhou, Zhen; Xie, Zhaojun
Abstract : The 5V spinel LiNi0.5 Mn1.5 O4 cathode materials with different morphology were prepared by a solid state calcination method and characterized by XRD, ICP, FE-SEM. Abstract : The 5V spinel LiNi0.5 Mn1.5 O4 cathode materials with different morphology were prepared by a solid state calcination method and characterized by X-ray diffraction (XRD), inductively coupled plasma (ICP), field emission scanning electron microscope (FE-SEM). Electrochemical properties of cathode material were investigated by electrochemical impedance spectroscopy (EIS), galvanostatic intermittent titration technique (GITT) and electrochemical performance tests. Compared with polycrystalline morphology (PLNMO), LiNi0.5 Mn1.5 O4 material with single crystalline morphology (SLNMO) proved smaller electrochemical polarization or voltage difference, lower internal resistance, faster lithium-ion diffusivity, arising from higher Mn 3+ content. Differential scanning calorimetry (DSC) showed that SLNMO was more stable than PLNMO at full charged state with organic electrolyte, which exhibited initial discharge capacity of 140.2 mA h g −1 at 0.1C, coulombic efficiency of 96.1%, and specific capacity retention of 89.2% after 200 cycles at 2.5C, a little inferior to that of 91.7% for PLNMO.